Retrospective Study Evaluating Seroprevalence of Hepatitis E Virus in Blood Donors and in Swine Veterinarians in Italy (2004). (2nd December 2016) - De Sabato, L.; Di Bartolo, I.; Montomoli, E.; Trombetta, C.; Ruggeri, F. M.; Ostanello, F.
Summary: Hepatitis E is an emerging viral disease in developed countries, with sporadic cases occasionally linked to the consumption of raw or undercooked pork, wild boar or deer meat. Cases due to transfusion or transplantation have also been reported. In developed countries, hepatitis E is considered a zoonosis and pig is the main reservoir. In the last few years, several studies conducted in Europe reported variable seroprevalence rates among the general population, ranging between 0.26% and 52.5%. A higher seroprevalence was described among workers who come in contact with pigs. The aim of this retrospective study was to evaluate the seroprevalence of anti‐HEV IgG and IgM antibodies in blood donors (170) and in pig veterinarians (83). Archival sera were collected in Italy in 2004. The observed seroprevalence was 9.64% and 8.82% in veterinarians and blood donors, respectively. Overall, only three sera from blood donors were positive for IgM, but no HEV‐RNA was detected.